The network of nitrifying and pathogenic prokaryotic interactions in a recirculating aquaculture system of a sole (Solea senegalensis) hatchery - Bastos Almeida, Diana; Semedo, Miguel; Magalhães, Catarina; Blanquet, Isidro; Mucha, Ana Paula (Frontiers in Marine Science, 2022)
Prokaryotic interactions in recirculating aquaculture systems (RAS) environmental communities may play a crucial role in driving their functional potential. However, these interactions are often neglected. The aim of this work is to detect prokaryotic interactions in a Solea senegalensis RAS, through the definition of relevant taxa and cluster identification using co-variance and co-occurrence tools. Amplicon sequence variants (ASV) were obtained from the water, tank biofilm, and biofilters of two systems, pre-ongrowing and weaning, and the study focuses on two microbial target groups, the potentially pathogenic and the nitrifying prokaryotes. No significant negative correlations were found with any target ASVs, indicating a mostly cooperative environment. As expected, ammonia oxidizing bacteria (Nitrosomonas) and archaea (Candidatus Nitrosopumilus) were found to be positively interacting with the nitrite oxidizing bacteria Nitrospira. However, no interactions were found between them, and results hint at a niche differentiation based on ammonia competition. Nitrospira also showed subcommunities with no ammonia oxidizing archaea or ammonia oxidizing bacteria correlations, hinting at a separate functional role of complete ammonia oxidation to nitrate for some Nitrospira ASVs. Two taxa commonly associated with pathogenic outbreaks, Tenacibaculum and Vibrio, had a significant positive correlation in one of the systems. With no outbreaks reported, this association may prove relevant in disease preventions and to improve outbreak predictions. Future studies may further elucidate this interaction, as cumulative evidence is still needed to better understand this correlation.